Understanding the diversity and evolution of complex wound infections - da Silva, Ana C. (2019)
Chronic wounds (CW) are a common complication of diabetic ulcers (DUs), which are a major burden to health care systems worldwide and can result in lower limb amputation due to the intractability of the infection. DUs appear because of underlying causes such as peripheral neuropathy, peripheral vascular disease and trauma and often become colonized with multiple microbial species including Staphylococcus aureus and Pseudomonas aeruginosa. Such polymicrobial infections have been suggested to be more virulent, antibiotic resistant and result in worse patient outcomes but the reasons why remain unclear.